Increasing Caregiver Knowledge about Long-Term Care with Interactive Educational Methods - Amigo, Thomas Aquino Erjinyuare; Nekada, Cornelia Dede Yoshima; Erwanto, Rizky; Kurniasih, Dwi Endah; Muflih, Muflih (Indonesian Journal of Global Health Research, 2024)
The growing number of elderly individuals requiring long-term care (LTC) necessitates caregivers enhancing their understanding of this care through interactive educational methods. As the elderly population grows, caregivers play a crucial role in providing long-term care (LTC) to the elderly and meeting their basic needs, including medical care, psychosocial support, and daily living skills. Interactive educational methods can enhance caregiver knowledge about LTC, enabling them to provide more effective and efficient care, especially for those lacking medical or health knowledge. The purpose of this study is to examine how interactive educational techniques have increased caregivers' understanding of long-term care. The research sample consisted of 11 health cadres in the Ngemplak Community Health Center working area with a purposive sampling technique. Researchers conducted a pre-test and post-test to measure knowledge before and after interactive education about long-term care. Wilcoxon's test results showed a p value of 0.004. There's a meaningful difference in knowledge between pre-interactive education and after interactive education. Caregivers can continue to follow a variety of training or education related to long-term care, be able to identify or screen elderly persons who need long-term care, learn about long-term care for parents on a sustainable basis, and provide long-lasting care to elders that focuses on meeting the basic needs of the elder.